Searches for superparticles at the LHC by application of computer simulation - Obikhod, T.V.; Malyuta, Yu.M. (Вопросы атомной науки и техники, 2013)
The analys of recent experimental data received from LHC (CMS) restricts the range of MSSM parameters to the new five parameters. Using computer programs SOFTSUSY, SDECAY and PYTHIA the mass spectrum, partial width and production cross sections of superpatners are calculated. In the context of Minimal Supersymmetric Standard Model histograms of mass distributions for superpartners qR and g are constructed. Аналiз останнiх експериментальних даних, отриманих на LHC, обмежив простiр MSSM параметрiв до нових п’яти параметрiв. Шляхом застосування комп’ютерних програм SOFTSUSY, SDECAY i PYTHIA розраховано маси, ширини розпадiв i перерiзи народження суперчастинок. У контекстi мiнiмальної суперсиметричної стандартної моделi побудованi гiстограми розподiлу мас суперчастинок qR и g. Анализ последних экспериментальных данных, полученных на LHC, ограничил пространство MSSM параметров до новых пяти параметров. Путем применения компьютерных программ SOFTSUSY, SDECAY и PYTHIA посчитаны массы, ширины распадов и сечения рождения суперчастиц. В контексте минимальной суперсимметричной стандартной модели построены гистограммы распределения масс суперчастиц qR и g.